Diffusion weighted imaging and diffusion tensor imaging in the evaluation of transplanted kidneys. (2015) - Palmucci, Stefano; Cappello, Giuseppina; Attinà, Giancarlo; Foti, Pietro Valerio; Siverino, Rita Olivia Anna; Roccasalva, Federica; Piccoli, Marina; Sinagra, Nunziata; Milone, Pietro; Veroux, Massimiliano; Ettorre, Giovanni Carlo
Abstract: Objective: The aim of this study is to investigate the relation between renal indexes and functional MRI in a population of kidney transplant recipients who underwent MR with diffusion-weighted imaging (DWI) and diffusion tensor imaging (DTI) of the transplanted graft. Method: Study population included 40 patients with single kidney transplant. The patients were divided into 3 groups, on the basis of creatinine clearance (CrCl) values calculated using Cockcroft-Gault formula: group A, including patients with normal renal function (CrCl ≥ 60 mL/min); group B, which refers to patients with moderate renal impairment (CrCl > 30 but <60 mL/min); and, finally, group C, which means severe renal deterioration (CrCl ≤ 30 mL/min). All patients were investigated with a 1.5 Tesla MRI scanner, acquiring DWI and DTI sequences. A Mann–Whitney U test was adopted to compare apparent diffusion coefficients (ADCs) and fractional anisotropy (FA) measurements between groups. Receiver operating characteristic (ROC) curves were created for prediction of normal renal function (group A) and renal failure (group C). Pearson correlation was performed between renal clearance and functional imaging parameter (ADC and FA), obtained for cortical and medullar regions. Results: Mann–Whitney U test revealed a highly significant difference ( p  < 0.01) between patients with low CrCl (group C) and normal CrCl (group A) considering both medullar ADC and FA and cortical ADC. Regarding contiguous groups, the difference between group B and C was highly significant ( p  < 0.01) for medullar ADC and significant ( p  < 0.05) for cortical ADC and medullar FA. No difference between these groups was found considering cortical FA. Analyzing groups A and B, we found a significant difference ( p  < 0.05) for medullar both ADC and FA, while no difference was found for cortical ADC and FA. Strongest Pearson correlation was found between CrCl and medullar ADC ( r  = 0.65). For predicting normal renal function or severe renal impairment, highest values of AUC were observed using medullar ADC cut-off values (respectively 0.885 and 0.871); medullar FA showed also high accuracy (respectively 0.831 and 0.853). Conclusions: DWI and DTI are promising tools for non-invasive monitoring of renal function; medullar ADC proved to be the best parameter for renal function assessment.